2009
DOI: 10.1373/clinchem.2008.108886
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of C-Reactive Protein in Atherothrombosis

Abstract: Background: Inflammation is pivotal in all phases of atherosclerosis. Among the numerous inflammatory biomarkers, the largest amount of published data supports a role for C-reactive protein (CRP) as a robust and independent risk marker in the prediction of primary and secondary adverse cardiovascular events. In addition to being a risk marker, there is much evidence indicating that CRP may indeed participate in atherogenesis. Content: In this review, we focus on the role of CRP in promoting athe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
182
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(196 citation statements)
references
References 84 publications
(102 reference statements)
5
182
0
9
Order By: Relevance
“…Thus, the measurement of circulating serum CRP is an important monitor of inflammatory disease in clinical routine [13]. Moreover, there is a rapidly increasing body of evidence that CRP levels can also be elevated in patients with chronic infections, artherosclerosis or malignant disease when compared to healthy controls [14][15][16][17][18]. Additionally, it has been shown that in many cancer types overall survival is strongly linked to and can reliably be predicted by pre-operative serum CRP levels [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the measurement of circulating serum CRP is an important monitor of inflammatory disease in clinical routine [13]. Moreover, there is a rapidly increasing body of evidence that CRP levels can also be elevated in patients with chronic infections, artherosclerosis or malignant disease when compared to healthy controls [14][15][16][17][18]. Additionally, it has been shown that in many cancer types overall survival is strongly linked to and can reliably be predicted by pre-operative serum CRP levels [19].…”
Section: Introductionmentioning
confidence: 99%
“…2 Synthesis and secretion of CRP via paracrine and autocrine pathways by cells of the atherosclerotic region results in CRP concentrations exceeding greatly the concentrations in plasma enhancing proinflammatory and proatherogenic effects. But the assumed prothrombogenic effects of CRP has been less well evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It is a pentraxin type of protein comprising of 5 noncovalently associated protomers arranged symmetrically around a central pore with a moleculat weight of 118000 Daltons. 2 Its gene has been mapped to chromosome 1. Its role is in clearing necrotic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CRP co-localizes with atherogenic mediators, including modified low density lipoproteins (LDL) [22,23], activated complement [24] and foam cells [20]. Together with the reported pro-inflammatory actions of CRP [25,26], including activation of complement and stimulation of expression of cytokines and adhesion molecules in endothelial cells, this protein is emerging as a promising drug target for CVD treatment [16]. Accordingly, a small molecule inhibitor that blocks the ligand binding site on CRP significantly reduced the complement-dependent infarction size in a rat model [27].…”
Section: The Controversial Role Of Crp In Atherosclerosismentioning
confidence: 99%